Pedagogical communication culture - Burkhonova D. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Pedagogical communication and its importance and the teacher's manners of dealing with students are discussed. Use of Eastern universal values ​​in teacher's activities. It is shown that the interaction takes place within the framework of mutual relations.